Human Rights In Islamic Law - Y. Sonafist (Pusat Publikasi Nusantara, 2023)
Many scholars write about textbooks on human rights both on a global scale and in Indonesia, but we find incompleteness on how human rights become practical and have value, a phrase in the book Human Rights Law. slightly) from the historical development of the birth of an understanding of human rights. And from an Islamic perspective we will read and see in the understanding of Islamic law itself. The problems inherent in human beings are something that attracts scientists, philosophers and also legal experts. Because in the human being itself is stored the will, rights and freedom that are inherent in him. Human rights (HAM) are rights that are owned by all people in accordance with humane conditions. Human problems are a matter of complexity, if the rights inherent in themselves are not fought for and protected, there will be social slavery, human colonization, and regulation. monolithic life. So that freedom and the will for independence should be restrained in the shackles of outside forces who